2020
DOI: 10.3390/ijms21134624
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Extracellular Vesicle-Derived TIMP-1 mRNA as a Prognostic Biomarker in Clear Cell Renal Cell Carcinoma: A Pilot Study

Abstract: The tumor microenvironment has gained a lot of attention from the scientific community since it has a proven impact in the development of tumor progression and metastasis. Extracellular vesicles (EVs) are now considered one of the key players of tumor microenvironment modulation. Clear cell renal cell carcinoma (ccRCC) is the most lethal urological neoplasia and presents a high metastatic potential, which reinforces the need for the development of more effective predictive biomarkers. Our goal was to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Concerning to metastatic ccRCC, an increase of EV-derived miR-301a-3p and a decrease of EV-derived miR-1293 is described [ 45 ]. Apart from miRNAs, EVs-derived tissue inhibitors of metalloproteinases (TIMP-1) mRNA are also included as good prognostic biomarker candidates for ccRCC [ 46 ]. In present work, we highlighted the role of EVs and focused on the strength of mtDNA as a relevant marker for both screening and aggressiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning to metastatic ccRCC, an increase of EV-derived miR-301a-3p and a decrease of EV-derived miR-1293 is described [ 45 ]. Apart from miRNAs, EVs-derived tissue inhibitors of metalloproteinases (TIMP-1) mRNA are also included as good prognostic biomarker candidates for ccRCC [ 46 ]. In present work, we highlighted the role of EVs and focused on the strength of mtDNA as a relevant marker for both screening and aggressiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that as a part of ECM, TIMP1 could led to accelerated differentiation and hypertrophy of adipocytes, which contributed to the pathogenesis of cancer [ 32 , 33 ]. A recent study showed that high TIMP1 mRNA was associated with a lower OS in clear cell renal cell carcinoma [ 34 ]. This is consistent with our results that a higher TIMP1 level was associated with poor OS in GAC patients.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence showed that the IGFBP2 levels are associated with cancer cell invasion and metastasis [ 23 , 24 , 25 ]; instead, IGFBP7 displays an ambiguous activity as an oncogene or suppressor gene in distinct types of cancers [ 26 ]. A pilot study demonstrated that TIMP-1 is a negative prognostic biomarker in clear cell RCC patients [ 27 ]; conversely, EDA-A2 is known to act as tumor suppressor when it binds its receptor, XEDAR [ 28 , 29 ]. Regarding NRG1, it has been recently demonstrated that it is released by the tumor microenvironment and promotes antiandrogen resistance in prostate cancer [ 30 ].…”
Section: Discussionmentioning
confidence: 99%